Position on The Arrangement of Administrative Sanctions By The KPPU Institution In State Science - Alsyam (Master of Law Program, Ekasakti University, 2024)
The position of the Business Competition Supervision Commission as a business competition court in imposing administrative sanctions (administration Punisment) to the guilty perpetrator. Looking at the constitutional system in a state institution in Indonesia, it has its own proportional functions in law enforcement. According to Article 36 letter i of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition that